D-DIMER PENDERITA SINDROM KORONER AKUT DAN STENOSIS - Birhasani .; Lisyani B S; Ria T (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Acute coronary syndrome (ACS) is the multisystem of coronary artery disease. The clinical manifestation of ACS is acute myocardialinfarction (AMI). About 90% coronary attack is caused by thrombus occlusion in coronary artery. The suspect of thrombosis can bediagnosed definitely by Angiography, but it is invasive. D-dimer used to measure thrombosis abnormality and fibrinolisys. The result oftheir correlation between D-dimer with ACS is still controversived. The aim of this research is to analyse, the different between plasmaD-dimer level ACS with stenosis ≥ 50% and stenosis < 50%. This study used a cross sectional design. The study consist of seventeenspecimen ACS with stenosis ≥ 50% and 17 specimen with stenosis < 50%. Plasma D-dimer level was measured with quantitativeagglutination latex method. An independent t-test statistical analysis is used in this study. The average Plasma D-dimer of ACS withstenosis ≥ 50% is 960.2 ± 404.99 µg/L thus ACS with stenosis < 50% is 300.3 ± 128.75 µg/L (p = 0.00). The plasma D-dimer levelof ACS with stenosis ≥ 50% is more significant than ACS with stenosis < 50%.